Estimation of cycle 25 parameters based on the rate of growth of solar activity - Єфіменко, Володимир Михайлович (Київський національний університет імені Тараса Шевченка, 2025)
Background. Solar activity is an important environmental factor. It is closely related to a number of geomagnetic phenomena, largely determines space weather, and has a profound impact on the space and terrestrial environment. Having reliable forecasts of solar activity, we can estimate these indices and the course of the natural processes associated with them. It should be noted that today there is still no sufficiently developed theoretical model for predicting solar activity for periods from several months to several years. Therefore, mathematical and statistical methods are used for practical forecasting for the specified periods. In addition to the height of the 25th cycle of activity, the assessment of the parameters of the current cycle is also of considerable interest, namely: the duration of the growth phase of the cycle and the full duration of the 25th cycle of solar activity. Methods. The method of constructing the dependences of the cycle height, the duration of the growth phase and the duration of the cycle on the rate of increase in activity using the known data of the 24 previous cycles was used. The determination of the coefficients of linear and polynomial dependences was performed using the OriginPro 8 software environment. The work refined the previously calculated forecast of the 25th cycle, estimated the duration of the growth phase and the full duration of the 25th cycle, taking into account the average rate of increase in activity in the growth phase of the 25th cycle and the obtained dependence coefficients. Results. The constructed dependences and the obtained coefficients in the equations made it possible to calculate the amplitude of the 25th cycle, which is Wmax 25 = 156.3 ± 14.4 units (the previously obtained cycle amplitude is within 150-160 units), as well as to calculate the duration of the growth phase and the full duration of the cycle. The durations of the growth phase and the total duration of the cycle were calculated using linear and polynomial dependencies. The values obtained are close to each other. Conclusions. The prediction of the amplitude of the 25th cycle was refined. The durations of the growth phase of the cycles were calculated from the rate of increase in activity. It was found that this dependence is quite high. The best result was obtained for the polynomial dependence (polynomial of degree 2) with R-Square (COD) = 0.84. In this case, the duration of the growth phase of the 25th cycle should be 57.8 months. For the linear dependence, we have the best result for the Pearson coefficient r = – 0.88. In this case, the duration of the growth phase of the 25th cycle should be 58.8 months. Based on the result obtained for the duration of the growth phase of the 25th cycle, an estimate of the duration of the 25th cycle was made based on the dependence of the cycle duration on the duration of the activity increase phase. The best result for the polynomial dependence for the 25th cycle is 11.5 years. For the linear dependence, we have the best result for the Pearson coefficient r = 0.56. In this case, the duration of the 25th cycle should be 11.2 years.

В с т у п . Сонячна активність є важливим фактором навколишнього середовища і має тісний зв'язок із низкою геомагнітних явищ, а також визначає космічну погоду, глибоко впливає на космічне і земне середовище. Маючи надійні прогнози сонячної активності, можемо оцінювати ці індекси і хід пов'язаних із ними природних процесів. Варто зазначити, що нині ще немає достатньо розробленої теоретичної моделі для прогнозування сонячної активності на терміни від кількох місяців до кількох років. Тому для практичного прогнозування на зазначені терміни застосовують математико-статистичні методи. Крім висоти 25 циклу активності значний інтерес становить також оцінювання параметрів поточного циклу, а саме: тривалості фази росту циклу і повна тривалість 25 циклу сонячної активності. М е т о д и . Використано метод побудови залежностей висоти циклу, тривалості фази росту і тривалості циклу від швидкості наростання активності за відомими даними 24 попередніх циклів. Визначення коефіцієнтів лінійної і поліноміальної залежностей виконано за допомогою програмного середовища OriginPro 8. Уточнено розрахований раніше прогноз 25 циклу, оцінено тривалість фази росту та повну тривалість 25 циклу з урахуванням середньої швидкості наростання активності на фазі росту 25 циклу й отриманих коефіцієнтів залежності. Р е з у л ь т а т и . Побудовані залежності й отримані коефіцієнти в рівняннях дали змогу розрахувати амплітуду 25 циклу, яка становить Wmax25 = 156.3 ± 14.4 одиниць (отримана раніше амплітуда циклу міститься в межах 150–160 одиниць), а також розрахувати тривалості фази росту і повну тривалість циклу. Тривалості фази росту і повну тривалість циклу розраховано з використанням лінійної і поліноміальної залежностей. Отримані при цьому величини близькі між собою. В и с н о в к и . Уточнено прогноз амплітуди 25 циклу. Розраховано тривалості фази росту циклів залежно від швидкості наростання активності. Визначено, що ця залежність є достатньо високою. Кращий результат отримано для поліноміальної залежності (поліном другого ступеня) з R-Square (COD) = 0.84. Причому тривалість фази росту 25 циклу має бути 57.8 місяців. Для лінійної залежності маємо кращий результат щодо коефіцієнта Пірсона r = –0.88. У цьому разі тривалість фази росту 25 циклу має становити 58.8 місяців. На підставі отриманого результату для тривалості фази росту 25 циклу оцінено тривалість 25 циклу на основі залежності тривалості циклу від тривалості фази наростання активності. Кращий результат для поліноміальної залежності для 25 циклу становить 11.5 років. Для лінійної залежності маємо кращий результат щодо коефіцієнта Пірсона r = 0.56. У цьому випадку тривалість 25 циклу має становити 11.2 років.
Оцінювання параметрів 25 циклу на основі швидкості росту сонячної активності
Keywords: сонячна активність; кількість сонячних плям; прогнози; максимум 25 циклу; тривалість фази росту; тривалість циклу; Сонце; Sun; solar activity; sunspot number; forecasts; maximum of the 25th cycle; duration of the growth phase; duration of the cycle